Preparation and evaluation of novel galantamine hydrobromide sustained-release capsule - Yang, Shuoye (Bangladesh Journal of Pharmacology, 2016)
In present study, a novel galantamine hydrobromide sustained-release capsule was prepared with the extrusion-spheronization method and the optimized preparative formulation. The release studies were performed using marketed capsules (Razadyne ER) as a reference and data were analyzed in terms of cumulative release amounts as a function of time. Furthermore, fiber-optic real time detection was adopted to monitor the release process. Results demonstrated that our developed formulation had superior properties, worked better as sustained-release carriers and lasted longer time to release compared with the marketed product. The in vitro release characteristics of different batches of preparations were quite similar with each other, the total release proportions of galantamine hydrobromide from sustained-release capsules reached higher than 90% within 12 hours. Similar factors f2 of two preparations were all higher than 50, the release profile of drugs from capsules fitted to Higuchi model with the equation of Q% = 0.2681t1/2 + 0.0684 (r = 0.9966). Pharmacokinetics profile and parameters in beagle dogs after oral administration also revealed the superior release performances of new capsules being consistent with the in vitro study. The developed sustained-release formulation may be a promising alternative dosage form for treatment of related diseases.